2013
DOI: 10.1111/ocr.12037
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different orthodontic appliances upon microbial communities

Abstract: The results suggest that orthodontic treatment may cause sustained changes in plaque microbiotas and that molar bond-associated plaque may have raised disease potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 29 publications
(38 reference statements)
0
71
0
2
Order By: Relevance
“…In 37 of the 52 articles presented with moderate methodological quality [921,2426,28,29,3133,3539,41–46,51–53,56,57], the major concern was the absence of repeatability tests. One article had a high quality [40] and the remaining 13 papers were classified as having a low quality [3,4,22,23,27,30,34,47–50,54,55].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 37 of the 52 articles presented with moderate methodological quality [921,2426,28,29,3133,3539,41–46,51–53,56,57], the major concern was the absence of repeatability tests. One article had a high quality [40] and the remaining 13 papers were classified as having a low quality [3,4,22,23,27,30,34,47–50,54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Eigh studies analyzed self-ligating braces (SLB) [9,14,24,3740,54]. Two studies [14,40] revealed no differences for BOP and PI between SLB and CB, while Nalçac et al and Uzuner et al [54] demonstrated a worsening in SLB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In orthodontics, the use of fixed appliances on teeth interferes with cleaning methods and can lead to plaque accumulation and potentially increased risk for periodontal diseases (19,20). Traditional culturing techniques have shown elevated numbers of periodontal pathogens, such as Porphyromonas gingivalis and Tannerella forsythia, present at the gingival margins during orthodontic treatment (21).…”
mentioning
confidence: 99%